Complexing Behaviour of 7-Bromo-2-methylamino-5-phenyl- 3H-1,4-benzodiazepine-4-oxide with Mn(II), Co(II) and Ni(II) and The Effect of Coordination on their Drug Potential - Zeinul Hukuman, N.H. (Asian Journal of Chemistry, 2010)
Synthesis of psychopharmacologically active complexes of divalent Mn, Ni and Co with 7- bromo-2-methylamino-5-phenyl-3H-1,4-benzodiazepine-4-oxide having ML4X2 stoichiometries have been reported (where X = Cl–, NO3– and CH3COO–). Characterizations have been done on the basis of elemental analysis, conductivity, magnetic, IR and electronic spectral studies. Complexes have been found as neuropharmacologically more effective in taming and hypnotic activities and possess much higher toxicity as compared to the ligand.